2018
DOI: 10.7717/peerj.5219
|View full text |Cite
|
Sign up to set email alerts
|

Hip muscular strength balance is associated with running economy in recreationally-trained endurance runners

Abstract: BackgroundThe percentage of sustained maximal oxygen uptake and the running economy are important factors that determine the running success of endurance athletes. Running economy is defined as the oxygen uptake required to run at a given speed and depends on metabolic, cardiorespiratory, biomechanical, neuromuscular, and anthropometric factors. With regard to anthropometric characteristics, total body mass seems to be a crucial factor for the running economy. Moreover, neuromuscular components, especially kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…All participants performed three sub-maximal trials to familiarise themselves with the test. As the most commonly used angular speed during isokinetic testing procedures is 60°s −1 , which has been suggested to reliably and accurately evaluate maximal capacities of the muscles to produce force ( Zapparoli and Riberto., 2017 ; Silva et al, 2018 ), five repetitions of concentric and eccentric isokinetic PT were evaluated on the knee and ankle joints at 60° s −1 in the present study ( Luna et al, 2012 ; Andrade et al, 2021 ). There was a rest period of 1 min between contraction type and a 10-min break between trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants performed three sub-maximal trials to familiarise themselves with the test. As the most commonly used angular speed during isokinetic testing procedures is 60°s −1 , which has been suggested to reliably and accurately evaluate maximal capacities of the muscles to produce force ( Zapparoli and Riberto., 2017 ; Silva et al, 2018 ), five repetitions of concentric and eccentric isokinetic PT were evaluated on the knee and ankle joints at 60° s −1 in the present study ( Luna et al, 2012 ; Andrade et al, 2021 ). There was a rest period of 1 min between contraction type and a 10-min break between trials.…”
Section: Methodsmentioning
confidence: 99%
“…To summary, regarding recreational runners, the benefits of neuromuscular factors on the RE have not been sufficiently studied ( Sundby and Gorelick, 2014 ; Silva et al, 2018 ; Lum et al, 2020 ). As the increasing number of recreational runners worldwide, identifying these key neuromuscular profiles may benefit runners as this knowledge could be applied to improve RE and running performance through a more optimal strength training program design.…”
Section: Introductionmentioning
confidence: 99%
“…These data were confirmed in two meta-analyzes: even in highly trained runners, strength training in addition to improving maximum power and strength, reduces the energy cost of running ( 14 , 15 ). Moreover, a greater hip flexor muscle strength relative to extensor muscle seems to be associated with a better RE, especially in male runners ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tatlici et al (2021) reported that 8-week wrestling training reduced the H/Q muscle ratio, strengthened the extensor quadriceps muscle, but did not cause a significant change in the strength of the flexor hamstring muscle, and recommended that specific hamstring exercises should be added to the training programs to prevent injuries. Studies have shown that the muscular balance in the lower extremities is related to the general body balance and oxygen utilization capacity, and that a developed muscular balance positively affects these parameters (Heitkamp et al, 2001;Silva et al, 2018). These variables are of vital importance for wrestling and it is known that an athlete with advanced motor features is advantageous during the wrestling match (Kuzmina et al, 2017;Moran-Navarro et al, 2015;Murlasits, 2004).…”
Section: Discussionmentioning
confidence: 99%